Effect of temperatures on development of Amrasca biguttula biguttula in transgenic Bt cotton - Boparai, Inderpreet Kaur Boparai; Kuma, Vijay (Indian Journal of Plant Protection, 2020)
The effect of different constant temperatures on development of cotton jassid, Amrasca biguttula biguttula was studied on Bt cotton cultivar, NCS 855 (BG II) during 2013 and 2014 under laboratory conditions in the Department of Entomology, Punjab Agricultural University (PAU), Ludhiana. Study conducted at constant temperatures of 22, 26 and 30 oC revealed that significantly higher nymphal survival, growth index and fecundity-cum-viability (76.67%, 7.61 and 13.50, respectively during 2013; 76.67, 6.94 and 12.67, respectively during 2014) occurred at 26 oC. Nymphal period, incubation period, male and female longevity and total development period were found to be significantly higher (12.98, 5.17, 11.60, 11.77 and 29.13, respectively during 2013; 13.73, 5.43, 12.45, 12.90 and 31.84, respectively during 2014) at 22 oC and it was lower at 30 oC during both the years. Sex ratio was found to be higher at 30 oC and it was lower at 22 oC. Nymphal period, male and female longevity had highly significant negative correlation with constant temperature.